Use of exogenous Xylanase for improvement of nutrient digestibility in broiler chicks - Moniz, Madison M.; Delfelder, C.J.; Beyer, R. Scott; Stark, Charles R.; Evans, C.E.; Yoder, Ashton D.; Jones, Cassandra K. (My University, 2017)
Due to consumers growing concern of the use of antimicrobials on livestock, the industry is working towards finding alternatives. Antimicrobials not only provide protection against bacterial infection but also help with nutrient digestibility. Exogenous xylanase is an enzyme that is known to improve nutrient digestibility in high fiber diets. However, there is no knowledge if exogenous xylanase can be used as a replacement for antimicrobials such as monensin sodium. Therefore, the objective of this experiment was to evaluate if xylanase can replace monensin sodium to improve nutrient digestibility, and if this impact differs based on the fiber level of the diet. A total of 216 Cobb 1-d-old chicks were fed 1 of 6 dietary treatments ad libitum in battery cages containing 6 birds per cage for 21 days. All 6 treatments were corn or wheat based formulated with either 0.10 g/kg monensin sodium (Coban 90; Elanco Animal Health, Greenfield, IN) or 16,000 betaxlylanse units/kg beta 1-4, endo-xylanase enzyme (Econase XT; AB Vista, Marlborough, UK). The two positive control diets consisted of corn plus monensin sodium and wheat plus monensin sodium. Neither of the positive control diets contained xylanase. The two negative control diets consisted of just corn and just wheat. Niether of the negative control diets contained monensin sodium or xylanase. The experimental diets consisted of corn plus xylanase and wheat plus xylanase. Neither of the experimental diets contained monensin sodium. Treatment impacted (P < 0.01) final BW, feed intake, and FCR. The corn-based control diet had improved (P < 0.05) FCR compared to the wheat-based control diet. In corn-based diets, neither the monensin sodium nor the xylanase improved (P > 0.05) FCR compared to the corn-based control. In wheat-based diets, xylanase (P < 0.05), but not monensin sodium (P > 0.05) improved FCR compared to the wheat-based control. In conclusion, this research suggests that xylanase improves carbohydrate digestibility in wheat-based diets, restoring FCR to that of corn-based diets. However, further research would need to be conducted to test its impact on bacterial prevention. Xylanase is not formulated to be an antimicrobial but can be tested in a floor-pen setting to see if there is an overall significant difference in health compared to birds being fed monensin sodium.
Keywords: Spring 2017